The Study of Goods and Services Tax on Multinational Companies in India - Arun Gautam; Gaurav Lodha; M.L. Vadera Vadera (International Journal of Supply Chain Management, 2019)
Although India has third largest economic growth,it can be much faster if we had an ideal tax system which collects taxes at different stages of manufacture, supply, wholesale, retailing and final consumption. These tax paid at different stages is not on the entire price but only on the value added. Keeping this in mind a new taxation system known as Goods and Services Tax (GST) was introduced in India, in order to remove the previous tax system which misses lead things and slower the economic growth. Due to the new introduction of the taxation system, many sectors of business were affected. Multinational Companies (MNCs) also faced changes.Import-export of MNCs, Customs duty application on MNCs and various effects on various MNCs are the things covered in this paper